The Role of Information Technology in Improving the Effectiveness of Education Management - Muhammad Sani Kurniawan (Departement of Mathematics Education, 2022)
Education is one of the important sectors in the development of a country. To achieve optimal education goals, effective and efficient education management is needed. However, the increasingly complex challenges in education management demand innovation and information technology as a solution. The purpose of this study is to explain the role of information technology in improving the effectiveness of education management in order to provide solutions and recommendations for the development of education in the future. The focus here is on qualitative analysis. Listening to and recording pertinent information was an integral part of data collection, which was followed by data reduction, data display, and inference. This study found that information technology plays an important role in improving the effectiveness of education management. In today's digital era, the use of information technology can help education management to obtain accurate, fast and easily accessible information, as well as facilitate distance learning and increase the accessibility and flexibility of learning. So, for various parties involved in education, it is necessary to improve digital literacy, including learners, educators, and education management.